(untitled) (Itinera, 2023)
The purpose of this study is to analyze some peculiar aspects on the conception of monsters and monstrous births in the centuries preceding the emergence of modern teratology. A “new” discipline, a branch of biology and, in particular, comparative embryology, whose scientific basis was laid by the studies of Etienne and Isidore Geoffroy Saint-Hilaire, in the first half of the nineteenth century. At the beginning I will show a brief summary of the multiple and heterogeneous theories which, in very different times, have tried to explain the causes of the nature and genesis of monsters. We will then go inside the very delicate question on the position of the soul, in man and monsters in particular, which had a direct influence on the possibility of saving from eternal oblivion, in the short time they usually survived, those small deformed creatures.